Digital Transformation in Educational Management: Impact Analysis and Implementation Strategy in LLDIKTI Main Cluster Colleges Region 2 with an Empirical Study at PGRI Palembang University - Putra, Muhammad Juliansyah; Lian, H. Bukman; Putra, Alhadiyan (Randwick International of Education and Linguistics Science Journal, 2025)
This study explores the impact and implementation strategies of digital transformation in educational management, with a focus on higher education institutions under LLDIKTI Region 2, using Universitas PGRI Palembang as a case study. Digital transformation in education management encompasses administrative processes, learning systems, and student services, leveraging technologies like Learning Management Systems (LMS), big data, and artificial intelligence (AI). The research identifies key challenges such as limited infrastructure, varied digital competencies, and resistance to change, as well as external factors like digital divides and policy dynamics. Using a descriptive quantitative approach with Results indicate significant operational efficiencies, enhanced educational quality, and increased transparency. The study recommends infrastructure upgrades, digital literacy programs, and stronger stakeholder engagement to optimize digital transformation efforts, offering a framework for broader adoption across similar institutions.